The potential of podshaving in studies of the role of trichomes in Vigna resistance to the podbug Clavigralla tomentosicollis Stal (Hemiptera: Coreidae) - Koona, P.; Jackai, L.E.N. (Springer, 2004)
Two shaving methods, one by using a sharp razor blade and the other a small pair of dissecting scissors, were tested on pods of Vigna vexillata accessions to investigate the effect of trichomes on feeding and development of the pod-bug Clavigralla tomentosicollis Stål (Hemiptera: Coreidae). Electron micrographs of unshaved (control) pods showed that all trichome types (glandular, long non-glandular and short non-glandular) were present on the pod surface. Shaving with a pair of scissors shortened long non-glandular trichomes, with little or no damage to the glandular types. Percentages of seed damage and nymphs surviving to the adult stage were similar (P>0.05) between unshaved and scissors-shaved pods. These pods showed significantly lower (P<0.05) percent seed damage than razor-shaved and solvent-washed pods, whose glandular trichomes were all completely scraped or washed off. The opposite trend was observed for the insect's growth index, indicating that glandular trichomes had a greater influence than non-glandular trichomes on feeding and development of C. tomentosicollis. The present study suggests that the scissor-shaving method would be more appropriate if the effect of trichome length is being investigated, and the more abrasive razor-shaving method if the effect of glandular trichomes is of interest.